Orientalism, Alterity and Social Identity : A historical analysis of the socio-psychological and socio-cultural dimensions of Afrikaner Nationalism, Antisemitism, and Jewish Identity in South Africa in the 1930s to the 1960s. - Mlambo, Prof. Alois (University of Pretoria, 2022)
Dissertation (MA (History))--University of Pretoria, 2021.